Recent vaccine related studies with economically important gastrointestinal nematode parasites of ruminants - Smith, W D (Tropical biomedicine, 2008)
Although several native antigens of sufficient efficacy to be commercially useful have now been discovered for Haemonchus and Ostertagia, all will have to be synthesised artificially to be economically viable. Despite numerous attempts, recombinant DNA technology has not yet yielded the solution, but the effort continues, spurred on by the successes with cestodes and certain ticks. Teladorsagia and Trichostrongylus lag behind in the vaccine research stakes: here, the first and probably most difficult step of identifying a reliably protective native antigen extract does not seem to have been achieved yet. It may be necessary to stimulate elements of the mucosal response to induce protection, a subject still in its infancy as far as ruminants are concerned. Several laboratories have started to work on antigen delivery methods with this in mind. It is easy to understand why intestinal antigens protect against blood feeding Haemonchus rather than mucosal browsers, but quite why conventional immunisation works for Ostertagia, but not apparently for Teladorsagia or Trichostrongylus remains a mystery.